The FT-IR spectroscopic investigation of two dimensional polymeric complexes of 2-aminopyrimidine - AKYÜZ, SEVİM (Elsevier, 2002)
The coordination polymeric compounds, M(2APM)2Ni(CN)4 (where M=Mn, Co, Ni or Cd; 2APM=2-aminopyrimidine) have been prepared for the first time and their FT-IR spectra are reported in the 400–4000 cm−1 region. The spectral features suggest that the compounds are similar in structure to the Hofmann type two dimensional coordination polymeric compounds, formed with Ni(CN)4−2 ions bridged by M(2APM)2+2 cations. 2APM is coordinated to M(II) through one of the pyrimidine ring nitrogen atoms; the amino group is not involved in the complex formation. The coordination effect on the 2APM vibrational wavenumbers is analysed. The coordination polymeric compounds, M(2-Aminopyrimidine)2Ni(CN)2 (M=Mn, Co, Ni, Cd) have been prepared and their FT-IR spectra are reported.
Keywords: Infrared spectra; Hofmann type complexes; Tetracyanonickelate; Transition metal; Aminopyrimidine